PENGARUH ABU VULKANIK KELUD DAN PUPUK KANDANG TERHADAP KETERSEDIAAN DAN SERAPAN SULFUR PADA JAGUNG DI TANAH ALFISOL - Suntoro S; Hery Widijanto; Sudadi S; Isni Wiyati (Ekosains, 2015)
A lot of sulphur in soil not available for plant. Kelud volcanic ash with cow manure added can use as an alternative to make nutrient sufficient for maize because it containt nutrients needed by plant. The aim of this research was to study the effect of Kelud volcanic ash thickness and cow manure dosage to sulphur availability and sulphur maize uptake on alfisol. The method of this research was Completly Random Design with two treatment factors. The first factor was Kelud volcanic ash thickness (0,2,4,6 cm), and the second factor was cow manure dosage (0; 2,5; 5 ton ha-1). Data analyzed with F test level of 95%, and if the treatment showed significant effect it was continued by Duncan's multiple range test level of 95%. The parameters of this reasearch were sulphur disolved, sulphhur maize uptake, maize height, fresh and dry matter of maize. The result showed that thickness of 4 and 6 cm Kelud volcanic ash significantly affected to sulphur availability and sulphur maize uptake. Furthermore, cow manure dosage of 2,5 and 5 ton ha-1 showed highly significant different to sulphur maize uptake than control. The best combination can not fixed because of both treatment factors non significant affected.